Ayer Hitam forest: the green lung of Klang Valley - Ibrahim, Faridah Hanum (Universiti Putra Malaysia Press, 2009)
Ayer Hitam Forest: The Green Lung of Klang Valley is illustrated with many colourful photographs and these represent some of the most splendid features of this biodiverse forest. Published with the financial support from Universiti Putra Malaysia, this book is intended to create better public awareness of the biodiversity it houses and the importance of its presence to the general public, the university and the environment in the vicinity specifically, and Klang Valley generally for now and the generations to come.